Analyzing the Effect of Product, Promotion and decision factors in Determining Green Purchase Intention: An Empirical Analysis - P. , Vijaya; M. , Sivakoti Reddy (International Journal of Psychosocial Rehabilitation, 2020)
Green products are eco-friendly and highly sustainable, widely acceptable for consumers health aspects. In this connotation, it is a considerable factor for a marketer to indulge himself to identify what consumers’ perceptions are about the company’s product and promotion factor that would intend the most and, in turn, lead to a green purchase decision. By intensive literature review, the three higher-order factors along with age, gender, and educational qualifications are considered in the present study, with price, product, and promotion as independent factors that influence green product purchase intention. An empirical examination was performed through a survey by considering the sample size of 151 respondents who purchase green products. Descriptive and inferential statistical techniques are performed, such as factor analysis and multiple regressions. By the observations, it is evident that demographics have a considerable intervention along with product and promotion on purchase intention, and subsequently, intention leads to a green purchase decision. Eventually, results along with discussions and conclusions are drawn in the study.